2021
DOI: 10.1097/sle.0000000000000952
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Appendectomy in the Days of COVID-19

Abstract: Background: Acute appendicitis is one of the most common emergencies treated by general surgeons. The treatment of choice in the majority of cases is laparoscopic appendectomy. In the era of the COVID-19 pandemic, there is a concern for a delayed referral of patients and thus a more advanced presentation of the disease leading to a prolonged and complicated course.Methods: Retrospective review of a computerized database of patients who were admitted with acute appendicitis and underwent laparoscopic appendecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another possible limitation of the study is that the COVID-19 pandemic occurred during the patient recruitment period, which spanned 2020–2021. During the first stage of the COVID-19 pandemic, there was a significant increase in the rate of complicated appendicitis [ 34 ]. In addition, a PCR test was added to the protocol, which could increase the hours of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible limitation of the study is that the COVID-19 pandemic occurred during the patient recruitment period, which spanned 2020–2021. During the first stage of the COVID-19 pandemic, there was a significant increase in the rate of complicated appendicitis [ 34 ]. In addition, a PCR test was added to the protocol, which could increase the hours of stay.…”
Section: Discussionmentioning
confidence: 99%
“…The hospital admission rates have dropped during the quarantine. We evaluated 25 studies related with COVID-19 and AAp, and 23 of these articles reported that there was a 24% (IQR: 15%-39%; min-max: 5.4%-81%) drop in the hospital admissions due to AAp during the quarantine regulations[ 1 - 4 , 10 , 12 , 14 - 22 , 33 - 39 ]. In only 1 of the 25 studies, there was a 7% increase in the hospital admissions[ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the 25 studies that were reviewed gave their results regarding negative appendectomy rates. The results of these studies showed that negative appendectomy rates dropped during the COVID-19 pandemic[ 1 , 6 , 13 - 16 , 18 , 33 , 34 , 39 ]. Five of the ten studies stated that this drop showed statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…This is the most common surgery that has been done in an emergency in large volume and exposed to all doctors at all healthcare centers frequently. [ 11 12 ] This surgery can improve skills in the laparoscopic mobilization of the bowel, intracorporeal knotting during ligation of the base of the appendix, dissection during handling mesoappendix or retrocecal appendix, and peritoneal lavage in case of an appendicular abscess. [ 13 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%